Effects of the Cooperative Learning-based Flipped Classroom Model on Chinese Students’ English Proficiency in the EFL Context - Meixiao Lin (JCTE, 2023)
This study investigates how the cooperative learning-based flipped classroom paradigm affects the English language ability of Chinese university students in an EFL (English as a Foreign Language) setting. It was decided to use a quasi-experimental study approach. In an integrated skills course, the experimental group engaged in flipped classroom activities based on cooperative learning (CL) for 80 minutes over the course of 24 sessions. Only standard whole-class instruction was given to the control class. The students’ spoken English proficiency was evaluated using an oral pre- and post-test before and after the intervention. The national written CET4 (College English Test Band 4) scores were adopted for comparing their general proficiency. The quantitative results revealed that the experimental class made greater gains in oral proficiency than the control class. Despite the fact that there was no significant difference in the written CET4 scores (general proficiency) between the two classes, the experimental class had a greater pass rate than the control class. The deployment of the CL-based flipped classroom paradigm in the EFL environment is further examined in connection to the results.